Advocacy for Social Transformation: Pancasila-Based Legal Education and the Street Law Model in Fostering Nationalism Among Youth in Kenteng Village - Wedhatami, Bayangsari; Arifin, Ridwan; Alkadri, Riska; Puspasari, Dewi; Ananta, Bintang Rafli (Indonesian Journal of Advocacy and Legal Services, 2024)
This paper investigates the role of Pancasila-based legal education through the Street Law model in advocating for social transformation and fostering nationalism among youth in Kenteng Village. As Indonesia strives to strengthen its national identity, particularly among younger generations, integrating Pancasila— the nation’s foundational ideology— into legal education becomes essential. The study outlines a community-driven program that engages university students and local youth in interactive legal workshops, promoting awareness of rights, responsibilities, and civic engagement rooted in Pancasila values. Through participatory methods, the program encourages youth to actively engage in discussions about legal issues and national identity, thereby enhancing their understanding of Indonesian democracy and governance. The findings reveal that this approach not only cultivates a sense of nationalism among participants but also empowers them to become advocates for their communities. Participants reported increased confidence in navigating legal matters and a stronger commitment to civic involvement. This research highlights the importance of advocacy in legal education as a catalyst for social change, demonstrating that the Street Law model can effectively bridge the gap between academic knowledge and practical application in the community. Ultimately, the paper argues for broader implementation of Pancasila-based legal education programs across Indonesia, suggesting that such initiatives can play a vital role in nurturing a generation of informed and engaged citizens dedicated to the ideals of Pancasila.